PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, DAN REWARD TERHADAP KINERJA PEGAWAI DI PERUM PEGADAIAN CABANG BESUKI - Agustyantono, Galang; Fadah, Isti; Titisari, Purnamie (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract: This study is aimed to analyze the effect of leadership, work environment,and reward on the employee’s performance at Perum Pegadaian Besuki. The population was all employees of Perum Pegadaian Besuki. The samples were consisted of32 respondents. Multiple linear regression was employed as the method of analysis. The results show that leadership has positive and significant effecton employee performance, work environment has positive and significant effect on employee performance, reward has positive and significant effect on employee performance,and leadership, work environment, and reward have positive and significant effect on employee performance of Perum Pegadaian Besuki. Keywords: Leadership, Work Environment, Reward, and Employee’s Performance